Inflammation and asthma - Nadel, J.A. (Journal of allergy and clinical immunology, 1984)
Extreme sensitivity of airways to multiple stimuli characterizes asthma. Airway hyperresponsiveness can be produced experimentally in otherwise healthy subjects or animals by inflammatory damage (e.g., induced by respiratory viruses or by inhaled oxidants). Evidence is presented that cell-to-cell interactions play an important role in experimental hyperreactivity and that similar inflammatory cascades may play a similar role in clinical asthma. Although the importance of epithelial cells and neutrophils has been identified in the present studies, other inflammatory mechanisms (e.g., sensory nerve release of substance P, epithelial mast cells, eosinophils) may also play key roles. In exercise-induced bronchospasm, the stimulus (e.g., cooling or drying) must affect a cell (e.g., one near the epithelial surface) by decreasing temperature or by increasing osmolality. This signal may cause mediator release and a subsequent cascade, leading to contraction of smooth muscle. Environmental irritants (e.g., ozone) inhaled during exercise may potentiate these effects by producing further inflammation.